Simulación de la caída de presión y de las condiciones acústicas en un sistema de escape convencional (2017)
This research project consists of the analysis of acoustic behavior and pressure drop, which are two determining factors in the design of automotive silencers. The present document provides a detailed compilation of information concerning the physical properties (pressure, velocity, temperature) of the fluid inside the exhaust system and the behavior of the sound waves in ducts and silencers. After this the properties of the fluid are determined and the sound propagation is analyzed with the finite element method in different topologies by means of the modeling and simulation in the ANSYS acoustic module, the transmission loss(TL) As an evaluative factor for acoustic performance in the different cases studied. For analysis of the pressure drop, the mesh convergence analysis is performed in NX, thus ensuring that the static pressure values ​​at the inlet and outlet of the silencer were valid for the calculation of the pressure drop. Finally, the results obtained in ANSYS are compared with those found in the literature.